Integrated approach for survival and development during first 1000 day of life: Assessing Health Systems Readiness in three Aspirational Districts of Jharkhand (India) - Jaya Swarup Mohanty; Anil Kumar Prabhanjan; Prasant Kumar Saboth; Harish Kumar; Enisha Sarin; Akay Minz; Shailesh Kumar Chourasia; Sachin Gupta (Wolters Kluwer Medknow Publications, 2021)
Introduction: With increased evidence of the association between early child-rearing practices and children's health, growth, and development, the government of India has introduced several policies and strategies, of which the home-based care for young child (HBYC) is the most recent. An assessment was conducted in three aspirational districts in Jharkhand to see system preparedness for implementation of the program. Material & Methods: Eight district key health personnel from 3 districts were interviewed on health systems readiness components. A total of 100 Sahiyas (Accredited Social Health Activists) and 100 mothers were selected across 8 villages in 2 blocks in each of the 3 districts of Lohardaga, Simdega, and West Singhbhum, and interviewed with a structured questionnaire on knowledge and practices. In addition, 24 auxiliary nurse midwifes, Sahiya Sathis, and Anganwadi workers were interviewed. Data collection teams underwent an orientation. Results: Most nodal persons were recruited; however, orientation to HBYC and awareness of key components such as incentives, supervision mechanism, and monitoring indicators was lacking. Supply of prophylactics and equipment was inadequate. Knowledge of community health workers was inadequate for many child care indicators except Oral Rehydration Salt (ORS) preparation (96%) and initiation of complementary feeding (97%). Knowledge of danger signs requiring referrals was particularly low (30%). Mothers' knowledge and practices were low on all the indicators. Conclusion: The HBYC program can build its success on the present health system functioning by tailoring trainings to focus on gaps in knowledge, addressing specific gaps in supplies, improving supervision, and integration efforts